2019
DOI: 10.1212/wnl.0000000000006878
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent stroke in midlife is associated with not having a primary care physician

Abstract: ObjectiveTo determine using a population-based study whether midlife stroke patients having a primary care physician (PCP) at the time of first stroke have a lower risk of stroke recurrence and mortality than those who do not have a PCP.MethodsFirst-ever ischemic stroke patients 45 to 64 years of age at stroke onset were ascertained through the Brain Attack Surveillance in Corpus Christi (BASIC) project from 2000 to 2013 in Texas. Cox proportional hazards models were used to examine the association between not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…One study reported on participants with a mean age of 20 years. Of the studies included, 20 reported solely the perspective of people with disability 35–37,39,40,42–45,47–50,57–59,61–64 . Four reported on the perspective of the person with a disability, as well as the GPs' perspective 38,46,55,56 and one paper reported on the perspective of the person with disabilities, alongside administrative data 54 .…”
Section: Resultsmentioning
confidence: 99%
“…One study reported on participants with a mean age of 20 years. Of the studies included, 20 reported solely the perspective of people with disability 35–37,39,40,42–45,47–50,57–59,61–64 . Four reported on the perspective of the person with a disability, as well as the GPs' perspective 38,46,55,56 and one paper reported on the perspective of the person with disabilities, alongside administrative data 54 .…”
Section: Resultsmentioning
confidence: 99%
“…A local study [ 14 ] including 705 acute ischemic stroke patients reported that 199 (28%) suffered further cerebrovascular cardiac events and 117 patients died (17%) during a follow-up period of 42 months. A US population-based study [ 15 ] including 663 first-ever ischemic stroke patients aged 45–64 years found the 5-year recurrent rate was 14.6% and mortality rate was 19.2%, respectively. We observed a lower recurrent stroke rate because of the following reasons: 1) patients had good control of blood pressure and DM at baseline; 2) the risk of recurrent stroke was highest in the first year [ 3 7 , 14 , 15 ] after the index stroke, and our cohort mainly consisted of patients with chronic stroke; 3) certain subgroup of stroke patients i.e., those with cardioembolic stroke, was not well presented in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A US population-based study [ 15 ] including 663 first-ever ischemic stroke patients aged 45–64 years found the 5-year recurrent rate was 14.6% and mortality rate was 19.2%, respectively. We observed a lower recurrent stroke rate because of the following reasons: 1) patients had good control of blood pressure and DM at baseline; 2) the risk of recurrent stroke was highest in the first year [ 3 7 , 14 , 15 ] after the index stroke, and our cohort mainly consisted of patients with chronic stroke; 3) certain subgroup of stroke patients i.e., those with cardioembolic stroke, was not well presented in our study. It is known that cardioembolic stroke survivors carries a higher risk for recurrent cardiovascular events [ 4 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tekrarlayan inme, ilk inme ile karşılaştırıldığında daha büyük mortalite, özürlülük ve maliyet oranına sahiptir. 13 İnme geçirmiş hastalarda, son yıllarda tekrarlama riski gittikçe artmaktadır. İnme geçiren hastalardaki risk faktörlerinin araştırılması, tekrarlayan inmelerin önlenmesi ve tedavisinde çok önemlidir.…”
Section: Discussionunclassified